Credit Ratings as Coordination Mechanisms - Arnoud W.A. Boot; Todd T. Milbourn (Tinbergen Institute, 2002)
In this article, we provide a novel rationale for credit ratings. The rationale that we propose is that credit ratings serve as a coordinating mechanism in situations where multiple equilibria can obtain. We show that credit ratings provide a focal point for firms and their investors, and explore the vital, but previously overlooked implicit contractual relationship between a credit rating agency (CRA) and a firm through its credit watch procedures. Credit ratings can help fix the desired equilibrium and as such play an economically meaningful role. Our model provides several empirical predictions and insights regarding the expected price impact of rating changes.
Keywords: 330; Kreditwürdigkeit; Implizite Kontrakte; Anlageverhalten; Theorie